Prevalence and correlates of social networking addiction and its association with adult ADHD and stress among students of a medical college - Abhishek Bahadur Singh; Ambrish Kumar Mishra; Mano Vijay; Varsha Karanth; Kailash Mittal (Wolters Kluwer Medknow Publications, 2023)
Introduction: Repeated use of social network is said to cause addiction. Attention deficit hyperactivity disorder (ADHD) is disorder found in childhood. Studies have shown that such children continue to have the symptoms of ADHD as adults. The aim of this study was to find the prevalence of social networking addiction and Internet addiction and their relationship with ADHD. Also, to assess the relationship between perceived stress and sociodemographic factors with social networking and internet addiction. Material and Methods: A cross-sectional study was conducted among 150 undergraduate and postgraduate students of BMCRI after ethical clearance. Medical students who gave consent were included through stratified random sampling. Those who were taking treatment for psychiatric illness were excluded. Scales like the Young Internet addiction test (IAT); Bergen's Facebook Reporting Scale, ADHD Self-Reporting Scale, and Wender Utah Brief Rating Scale for ADHD, and Cohen Perceived Stress Scale (PSS) for perceived stress have been used. Results: The mean age was found to be 21.56 ± 3 years. 62.6% were males and 37.33% of were females. The prevalence of Internet addiction was found to be 23.3% (n = 35), with 2% (n = 3) were having severe addiction, 6.6% (n = 10) were having moderate Internet and 14.6% (n = 22) having mild internet addiction according to modified Young's criteria (2011). The prevalence of social networking addiction as per the Bergen Facebook Addiction Scale (BFAS) score was 4.66% and adult ADHD was 15%. There was a strong positive correlation (0.76) between Internet Addiction and Facebook addiction scores and between BFAS score and IAT score. A moderate positive correlation (0.46 and 0.47) between Internet addiction and Facebook addiction with perceived stress and ADHD and IAT score with PSS score and ASRS score, weak positive correlation with PSS score and ASRS score was observed. Conclusion: A significant proportion of medical students develop Internet addiction and minority develops social network addiction. Furthermore, perceived stress and ADHD scores are positively correlated with internet and social networking addiction.